Chemoprevention Studies of the Flavonoids Quercetin and Rutin in Normal and Azoxymethane Treated Mouse Colon - YANG, K. (Institutional Knowledge at Singapore Management University, 2000)
In this study we investigated the chemopreventive effects of quercetin and rutin when added to standard AIN-76A diet and fed to normal and azoxymethane (AOM)-treated mice. Early changes in colonic mucosa were analyzed, including colonic cell proliferation, apoptotic cell death, cyclin D1 expression and focal areas of dysplasia (FAD). The findings show that the number of colonic epithelial cells per crypt column increased (P < 0.01) in each normal mouse group fed the flavonoids; AOM administration increased colonic crypt cell proliferation and resulted in a marked rise of bromodeoxyuridine-labeled cells in the lower proliferative zone of the crypt. Both supplementary dietary quercetin and rutin increased the apoptotic index and caused a redistribution of apoptotic cells along the crypt axis in normal mice fed a standard AIN-76A diet. The number of apoptotic cells/column and apoptotic indices markedly increased (P < 0.01) in the AOM-treated group compared with untreated animals; apoptotic cells expanded throughout the colonic crypts after flavonoid supplementation and AOM administration. Positive cyclin D1 expression was detected in mice on diets supplemented either with quercetin (P < 0.01) or rutin (P < 0.05). AOM administration resulted in the formation of FAD. Both the number of mice exhibiting FAD and the total numer of FAD observed were significantly reduced (P < 0.01) in AOM-treated animals fed flavonoids compared with mice maintained on the standard AIN-76A diet. Surprisingly, however, quercetin alone was able to induce FAD in 22% of normal mice fed the standard AIN-76A diet.